ANALYSIS OF THE RELATIONSHIP BETWEEN HEALTH CENTER SERVICE QUALITY AND ELDERLY PATIENT SATISFACTION AT GONDANGLEGI HEALTH CENTRE - Azizah, Lilik Nur (Transpublika Publisher, 2022)
This study aims to analyze the relationship between Service Quality of Health Centre and elderly patient satisfaction at Gondanglegi Health Centre. This study is correlation analysis with cross sectional approach. The sample was taken by consecutive sampling technique with a sample was obtained 49 respondents. The data was collected by questionnaires and interviews. The data processing uses editing, coding, scoring and tabulating and statistical tests using Mann Whitney. The findings reveal that the quality of health services for the elderly at the Gondanglegi Health Centre in Malang Regency is almost half good. Meanwhile, the satisfaction of elderly patients is almost half of the satisfied patients. On the other hand, there is a relationship between the quality of health care services with the satisfaction of elderly patients at the Gondanglegi Public Health Centre.